Agnostics’ Well-Being Compared to Believers and Atheists: A Study in Europe’s Religious–Cultural Zones of Christian Heritage - Moise Karim; Vassilis Saroglou (Religions, 2024)
Past research suggests three distinct major trends regarding the links of religion with well-being. First, religious faith contributes to well-being, with believers showing higher well-being than nonbelievers. Alternatively, it is certainty about one’s own worldviews, be they religious or irreligious, that predicts well-being. Finally, secularization moderates the above, making nonbelief normative. We investigated these trends by focusing on agnostics, who, compared to believers and atheists, combine a lack of faith and uncertainty about worldviews and should, thus, be the lowest in well-being. By analyzing European Values Study 2017 data from 29 countries and controlling for personal variables, we found that in countries of Western Christian heritage, be they religious or secularized, agnostics were the least happy compared to believers and atheists. Religionists, compared to atheists, were happier (countries of Protestant heritage) or equally happy (countries of Catholic heritage). In countries of Eastern Orthodox tradition, believers were happier than nonbelievers, agnostics, and atheists alike—but again, agnostics were the lowest in the less religious countries. In sum, uncertainty makes agnostics, consistently across religious cultures, to be the lowest in well-being, whereas the effect of religious faith on well-being varies across cultures.